Endoillumination Assisted Scleral Buckling: The future Approach to Retinal Detachment Surgery - Pradeep Venkatesh; Tarun Arora; Satpal Garg (Delhi Journal of Ophthalmology)
Rhegmatogenous retinal detachment is presently managed by conventional scleral buckling, pneumatic retinopexy or vitreoretinal surgery. To do away with the need for indirect ophthalmoscopy surgeons are now more inclined towards primary vitreoretinal surgery even in simple retinal detachment. However, standard three port vitreous surgery also carries with it disadvantages like progression of cataract, creation of iatrogenic tears, placement of long acting vitreous substitutes like intraocular gas or silicone oil, silicone oil glaucoma, andsilicone oil keratopathy. To overcome the above disadvantages of a full fledged vitreoretinal surgery in patients with simple retinal detachments, we hypothesize the possibility of achieving good results with an alternate surgical approach to carry out conventional buckling surgery – the endoilluminator assisted scleral buckling. With this approach it is not only possible to locate the number and location of breaks more accurately while seated at the microscope, but also undertake cryopexy of the breaks, drainage of subretinal fluid at a site wherein the height of detachment is maximum and also titrate the buckle height to achieve an ideal buckle-break relationship. This new approach hence combines the advantages of visualization provided by vitreoretinal instruments (endoillumination and wide angle viewing) and safety and simplicity ofconventional scleral buckling surgery.